하악 전방부에 발생한 복잡치아종의 치험례 - 이제우 (대한구강악안면병리학회지, 40(2), 2016)
Odontomas are mixed odontogenic tumors in which both the epithelial and mesenchymal components have undergone functional differentiation. Two types of odonotma are histomorphologically recognized: complex and compound. Complex odontomas have little or no morphologic similarity to normal tooth formation, and they commonly found in the posterior mandible. They are typically asymptomatic, and the most common presenting symptom is usually lack of eruption of a permanent tooth. The recommended treatment for an odontoma is conservative surgical excision. No tendency for recurrence has been noted. An eight-year-old girl was presented with swollen mouth floor. Radiographically, there were radiopaque mass on anterior mandible with impacted lower left central incisor. Under midazolam intraoral sedation and N2O-O2 inhalation sedation, the odontomas were surgically removed. The diagnosis was complex odontoma. After follow-up of 28 months period, there was no recurrence. The impacted tooth erupted spontaneously and the space for the erupted tooth was regained orthodontically. KCI Citation Count: 0